Deep Brain Stimulation for Obsessive-Compulsive Disorder: Real World Experience Post-FDA-Humanitarian Use Device Approval - Kahn, Lora; Sutton, Brianne; Winston, Helena R.; Abosch, Aviva; Thompson, John A.; Davis, Rachel A. (Frontiers in Psychiatry, 2021)
Background: While case series have established the efficacy of deep brain stimulation (DBS) in treating obsessive-compulsive disorder (OCD), it has been our experience that few OCD patients present without comorbidities that affect outcomes associated with DBS treatment. Here we present our experience with DBS therapy for OCD in patients who all have a comorbid disease, together with the results of our programming strategies. Methods: For this case series, we assessed five patients who underwent ventral capsule/ventral striatum (VC/VS) DBS for OCD between 2015 and 2019 at the University of Colorado Hospital. Every patient in this cohort exhibited comorbidities, including, various substance use disorders, tic disorder, and autism spectrum disorder. We conducted an IRB-approved, retrospective study of programming modifications and treatment response over the course of DBS therapy. Results: In addition to patients’ subjective reports of improvement, we observed significant improvement in the Yale-Brown Obsessive-Compulsive Scale (44%), the Montgomery-Asberg Depression Rating Scale (53%), and the Quality of Life Enjoyment and Satisfaction Questionnaire (27%), Young Mania Rating Scale (32.4%), and the Hamilton Anxiety Rating scales (34.9%), following DBS. With respect to co-morbid disease, there was a significant improvement in a patient with Tourette’s Total Tic Severity Score (TTSS) (p=0.005). Conclusions: DBS remains an efficacious tool for the treatment of OCD, even in patients with significant comorbidities in whom DBS has not previously been investigated. Efficacious treatment results not only from the accurate placement of the electrodes by the surgeon but also from programming by the clinician.